CT-Guided Percutaneous Radiofrequency Thermocoagulation for Recurrent Trigeminal Neuralgia After Microvascular Decompression: A Cohort Study - Lai, Guang-Hui (Medicine (Baltimore), 2015)
This article evaluates the long-term outcomes of computed tomography (CT)-guided percutaneous radiofrequency thermocoagulation (PRT) for patients with recurrent trigeminal neuralgia (TN) after microvascular decompression (MVD). This is a retrospective study of 41 patients with intractable TN who after MVD underwent CT-guided PRT procedures between 2002 and 2012. The mean length of follow-up after PRT was 44.4 months. Immediate pain relief was in 37 patients (90.2%); the percentage of patients who remained in “excellent” or “good” pain relief condition after CT-guided PRT procedure was 85% at 1 year, 80% at 2 years, 51% at 5 years, and 41% at 10 years. Six patients received the second PRT and all achieved “excellent” or “good” pain relief. In total, 34 of these patients (82.9%) received multi-PRT procedure and remained satisfied with their pain relief during the follow-up period. Postoperative complications included facial numbness in 36 patients, limited eyes opening in 1 patient, ear paresthesia in 1 patient, no tears in 1 patient, and taste hypesthesia in 1 patient; these symptoms were all improved in the process of follow-up and their life had not severely affected. No mortality was observed during and after CT-guided PRT procedures. CT-guided PRT should be considered as an alternative treatment for patients with recurrent TN after MVD.